Deterrent Effect of Punishment on the Offender (a Review of Empirical Research) (Archives of Criminology, 1995)
The number of studies on specific deterrence is not large. Some data on this subject can be found in other studies aimed e.g. at evalution of effectiveness of diffrent penal measures, or analysis of criminal careers. One of the reasons of this lack of interest in specific deterrence is a belief,  rather common today and particularly marked in the 1960s, that punishment not only fails to deter the convicted person from futher offenses but – quite the contrary - increases the probability of his futher criminal carrer.  Another reason is probably the great difficulty in distinguishing for research purposes of the impact of specific deterrence from the other effects of punishment. Unfortunately, a statement made by J. Gibbs over twenty years ago still remains valid: there is no theory of specific deterrence, and the hypotheses concerning specific deterrence are vague and difficult to verify empirically.During the last twenty  years, there was a progress in the methodology of research into specific deterrence. New success criteria were introduced into the assessment of deterrent effect of punishment, and the method of random field experiment was used. Researchers started to compare the effect of punishment with the effects of escaning punishment, instead of limiting themselves to comparisons of relative effectiveness of some penalties as opposed to some other ones. The progress was less marked in the formation of the theory of specific  deterrence. It consists in attempts, on the one hand, at a new conceptualization of the problem of deterrence, and on the other hand, at integrating the deterrence hypothesis with other theoretical approaches.The paper consists of seven parts. The Introduction (I) contains analysis of the notion of specific deterrence, the criteria to distinguish between specific and general deterrence, tvpes of deterrence. Also discussed have the recent attempts at a new conceptualization of tne problem of deterrence through inclusion into that notion of not only the “direct costs of legal sanctions” but also “indirect costs”, or through the use of another criterion to distinguish between specific and general deterrence.Chapter II contains a brief discussion of early studies on specific deterrence; the findings have been discussed and numerous methodological flaws pointed out. The conclusion from those studies (that severe penalties involve a higher recidivism rate than lenient penalties) was generally seen as a prove that punishment has no specific deterrent effect on the futher behaviour of convicted persons. This conclusion was unjustified, though. And that for several reasons. The discussed studies often failed to distinguish between the mechanism of deterrence and the other effects of punishment. They also failed to solve the problem of selection bias in sentencing where specific types of penalties are imposed on specific categories of offenders; the difference between such groups of convicted persons is that even before the imposition of penalty, the probability of their relapse into crime was different. The studies examined but a marginal effectiveness of some  penalties as compared to some other ones. What they overlooked, instead, was that the growth in recidivism rate cannot be estimated which would have taken place were no criminal penalties at all imposed on offenders.Chapter III discusses the findings of studies which tested two opposing hypotheses; i.e. that punishment either deters offenders (deterrence hypothesis) or amplifies offendling (amplification hypothesis). Both the conception of deterrence and that of labeling involve too one-sided and simplified an approach to the impact of punishment on the further conduct of offenders as they ignore the possibility of effects  other than the anticipated ones. This was reflected in these studies in which the researches posed instead of posing questions in the categories of “whether” (does punishment deter? does pinishment amplify affending?), instead of trying to define the conditions of emergence of each of those two effects. Analyzed in few studies only were mediating psycho-social processes between punisment and the punished pefsons’ further conduct. The findings of different studies are often inconsistent. Some seem to confirm the amplification hypothesis although researchers sometimes stress that this effect is not stable Other findings point  to the effect of deterrence. Still other studies showed that: punishment seems do not influence a pefson’s further criminal career. Finally, some of the latest findings also indicate the possibility of amplifijing offending under some conditions and of deterring effect on offending - under some other circumstances.Chapter IV discusses the implications of the criminal careers approach formethodology of studies on specific deterrence. What is particularly worthy of attention here is: 1) departure from the use of a sole success criterion in the evaluation of deterrent effect of punishment, and an attempt at grasping the impactof punishment on different dimensions of criminality such as the length of criminal career or fraquency of offenses; 2) investigation of the impact of punishment at different stages of a person’s criminal career. The success criterion  where success means a person’s abstention from further offenses is replaced with the before and after comparison criterion where the intensity of a person’s criminal career before and after punishment is compared; this replacement is of a great importance in studies of effectiveness of penal  measures imposed on chronic offnders. As suggested by the findings, certain penalties may in cessation of delinquency at the initial stage of the criminal career (on the occasion of the first and possibly also the second contact with the police). At further stages of that career, a decrease in the intensity of delinquency of the persons convicted is possible.Chapter V discusses attempts at including the hypothesis of  specific deterrence into the economic model of delinquent behawior, and studies carried out by economists. According to some economists, specific deterrence can be included into the theory of rational choice provided it is treated as a special case of general deterrence. In tlis approach, the experience of a sanction becomes a factor influencing the anticipated sanctions.Chapter VI is devoted to discussion of the results of a series of rondom fieldexperiments conducted in selected cities of the United States. The purpose was toevaluate the effectiveness of arrest as compared to other reactions to violence against a spouse (nearly all victims in the study were women). The obtained results were not uniform: in some experiments, deterrent effect of arrest was found out, while the rest showed an amplifying effect of arrest on the arrested person’s  further violence against his spouse. The authors explain this divergence of results with a different impact of arrest on different types of persons. Thus the results suggest that arrest has  a deterrent effect on permanently employed suspects; instead, suspects without a regular job tended to use violence more often after the  arrest incident.The last Chapter (VII) recapitulates the findings. They show that it was a premature decision to reject the hyphothesis of specific deterrence. Punishment has a different impact on different persons: in some situations it results in amplication of offending; in some other ones, it deters a person from further offenses; and  in still other situations it seems not to have any effect at all on furter offending. The findings point to a great importance in this respect of the first contacts with the law enforcement agencies. Moreover, the differentiated effect of punishment seems to depend on the offender’s age, sex, and attitude towards risk, and also on his permanent employment. It should be stressed that many studies use a broader definition of punishment, not limited to the penalties  imposed by court. Some researchers treat even a person’s contact with the police as punishment; others believe that this function is performed by arrest. These different working definitions of punishment make it difficult to interpret the findings that relate to absolute deterrence, that is assessment of the effects of imposing punishment as compared to those of escaping punishment. Nearly all studies dealt with recidivism and, first and foremost, the effectiveness of punishment in reducing a person’s further delinquency. To a slight extent only did they try to define the meaning of punishment for those punished, their subjective estimations of probability and severity of punishment. For this reason, interpretation of the findings in the categories of stating whether punishment has a deterrent effect is not always justified.